2015
DOI: 10.1093/cid/civ066
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Outcomes of Hematogenous Vertebral Osteomyelitis With Instrumented Surgery

Abstract: Spinal instrumentation in patients with HVO may be safe with pathogen-directed prolonged antibiotic therapy and should not be abandoned or delayed solely because of the risk of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 25 publications
4
52
2
1
Order By: Relevance
“…35,1822 It even reaches 100% in case of postoperative spondylodiscitis. 18 This variation is probably due to the lack of consensual definition of the neurological impairment across studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35,1822 It even reaches 100% in case of postoperative spondylodiscitis. 18 This variation is probably due to the lack of consensual definition of the neurological impairment across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mc Henry in his large cohort of spontaneous and postoperative VO found 25% of motor deficit mainly caused by a compressive myelopathy, compressive radiculopathy, or cauda equina syndrome. 19 In a recent large neurosurgical population of 153 patients Park et al 3 showed 23.5% of “neurological deficit” but precisions about neurological examination were not given. Another recent study conducted by Bernard et al 5 found 16% of neurological signs at baseline, including 5% of motor deficit and 11% of sciatica.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary failure was defined as patients who needed another episode of surgical debridement after surgical intervention before the completion of antibiotic treatment because of signs of uncontrolled infection. Recurrence was defined as patients with recurrent symptoms and signs after the completion of antibiotic therapy and who received a second course of parenteral antibiotic treatment12).…”
Section: Methodsmentioning
confidence: 99%
“…2 Median patient age was 59 (interquartile range [IQR]: 49-67), and 25 (64%) patients were male. According to the Child-Pugh classes, 13% of patients were defined as grade A, 54% as grade B, and 33% as grade C. Back pain and fever were the most common symptoms.…”
mentioning
confidence: 99%